Boni In Chinese Sources From The Tenth To The Eighteenth Century - L. Kurz, Johannes (Penerbit Universiti Sains Malaysia (USM Press), 2014)
The present national history of the Sultanate of Brunei includes a fabricated history of official Brunei-China relations that extends as far back as the sixth century AD. The present paper treats the subject of Boni, a place well documented by pre-modern Chinese sources starting from the tenth century. It attempts to address some major issues in the use of these sources to establish Boni as a precursor of modern Brunei. Since the late 1970s writers within Brunei, foremost among them Robert Nicholl, have contributed to the project of a long history of pre-modern Brunei by interpreting the available Chinese sources very narrowly. Based on a close reading of the original texts, this essay argues that the majority of the texts until the Ming dynasty quote from the first extant source in the tenth century. Hence, official Chinese perception of Boni did not increase over time, but in fact did stagnate. Consequently, identification with a specific location in Borneo, as Nicholl and C. Brown suggested, is impossible. What the essay suggests is that with the extant official pre-modern Chinese texts Boni cannot be established as Brunei, but that more likely, Boni under different dynasties referred to various places on the north coast of Borneo